Support care needs of Filipino parents of children with cancer - Banayat, Aprille Campos (Manila: College of Nursing, University of the Philippines Manila, 2019)
This study was able to explore the care needs of parents of children with cancer. With embedded mixed method design, it used the quantitative rCPNQ survey and qualitative semi-structured interviews to describe the care needs, identify associations, and explore the priorities and perspectives of parents in addressing their care needs. -- Filipino parents of children with cancer have various care needs and could be classified along the categories of the supportive care needs framework - practical, informational, spiritual, physical, emotional, and physical needs as ranked from the highest to the lowest in this study, respectively. -- A number of variables are significantly associated to the care needs. Type of diagnosis is associated with psychosocial and emotional care needs. Surgery is associated with spiritual and emotional needs. Length of time since diagnosis is associated with informational, spiritual, and physical needs. Interestingly, no variable is associated to practical needs. -- Priorities include (1) practical needs throughout the experience; (2) informational needs on sources of financial assistance; (3) spirituality to solve other care needs; and (4) precedence of needs of the child over their (parents) own needs. On the other hand, perspectives in addressing the care needs include: (1) addressing financial needs; (2) role of half-way houses; (3) bayanihan: support groups among parents of children with cancer; (4) using prayer to facilitate acceptance; (5) damayan: support between members of the family and spouses of parents of children with cancer. -- Care needs of parents of children with cancer is an important component of care that should be given recognition throughout the childhood cancer experience.
Thesis (Master of Arts in Nursing - Maternal and Child Nursing) -- University of the Philippines Manila, June 2019.
Bibliographical references: 99-111 leaves.
Keywords: Cancer in children; Parents of chronically ill children